Numerical Studies of Premixed and Diffusion Meso/Micro-Scale Flames - Cova, A.; Resende, P. R. [UNESP]; Cuoci, A.; Ayoobi, M.; Afonso, A. M.; Pinho, C. T. (Elsevier, 2017)
This work reports a numerical investigation of premixed and diffusion meso/micro-scale flames, with homogeneous reactions, for two different cases involving CH4/air premixed dynamics flames and co-flow diffusion flame with H2/N2 mixture. In the first case, the numerical predictions are able to capture the flame characteristics behaviour for different fuel equivalent ratio and geometries, showing the accuracy of the reactions model, which uses a very detailed kinetics. In the second case, the analysis concerns the effect of a porous bluff body in pollutants emissions, especially the NOx formation, at meso scale, considering different porous temperatures and geometrical configurations.
Keywords: diffusion; dynamics flames; Micro-flames; numerical simulation; porous bluff body